The comorbidity of diabetes mellitus and psychiatric disorders - Medved, Vesna (Array, 2009)
Diabetes mellitus is a chronic disease affecting approximately 6% of the general population. Depression and schizophrenia are often comorbid with diabetes. There are two main ways to explain this phenomenon. Firstly, patients with diabetes mellitus have higher incidence of psychiatric disorders and secondly, antidepressants and antipsychotics may cause metabolic abnormalities. Antidepressants with noradrenergic activity have the highest potential to cause metabolic abnormalities. In schizophrenia, the risk is highest with clozapine and olanzapine pose the highest risk, moderate for risperidone and quetiapine, while ziprasidone and sertindole have not been associated with diabetes. During the first three months, weight gain should be monitored on monthly basis, while biochemical analysis should be performed after the first three months, and then once a year. In patients with significant weight gain, increase of blood glucose level or dyslipidemia, the first intervention should be switch to another antipsychotic. If necessary, a patient should be referred to an endocrinologist and advised on changing their life style